Evaluation of concentrated vinasse as additive in replacement pullets - Hidalgo, Katia; Valdivié, M.; Bocourt, R.; Mora, L. (Cuban Journal of Agricultural Science, 2020)
In order to evaluate concentrated vinasse as additive in productive and reproductive indicators of replacement pullets, 960 White Leghorn L33 pullets, between 1 and 18 weeks old, were used. A diet with corn and soybean was used, with the addition of 0, 1.0, 1.5 and 2.0 % of concentrated vinasse of sugar cane per pullet/day, calculated based on dry matter. Weights at the end of rearing were below the standards, due to the early sexual maturity reached by the pullets at 18 weeks. Viability and uniformity of animals were excellent in all treatments, in a range between 93.73 and 97.28 %, and from 94.15 to 97.49, respectively. However, they were superior for 1 % of vinasse inclusion. In reproductive indicators, with the increase of the level of inclusion, the ovary weight also increased (1.88, 3.63, 4.63 and 5.88 g), as well as the number of follicles (>2 mm). The length of the oviduct of pullets had the same performance, with a dependence between growth and inclusion level. All this allowed to start the laying between 17 and 18 weeks. These results demonstrate that including concentrated vinasse as additive in the diet of replacement pullets allows to obtain animals with early sexual maturity and better preparation for future egg production. Key words: pullets, distillery wastes, reproductive indicators, productive performance